1995
DOI: 10.1258/002367795781088306
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme-linked immunosorbent assay (ELISA) for monitoring rodent colonies for Pasteurella pneumotropica antibodies

Abstract: An enzyme-linked immunosorbent assay (ELISA) was developed for the detection of Pasteurella pneumotropica antibodies in the sera of rats, mice, hamsters and Mastomys. P. pneumotropica from mice and rats showed cross-reactivity. The ELISA using P. pneumotropica NCTC 8284 detected more infected animals than selective culture in groups of rodents from which P. pneumotropica, Haemophilus sp and/or Actinobacillus sp were cultured. Cross reactivity between P. pneumotropica NCTC 8284 and haemophilus and actinobacillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The WCA-based ELISA established by our group appears to provide a much higher sensitivity and to differentiate defined positive sera of the two closely related Rodentibacter species. Apparently, the new test improves previously reported WCA-based ELISA protocols [12, 21]. Generally, the reported prevalence may be influenced by insensitive ELISA assays used in routine health monitoring, as shown here for one commercial assay.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The WCA-based ELISA established by our group appears to provide a much higher sensitivity and to differentiate defined positive sera of the two closely related Rodentibacter species. Apparently, the new test improves previously reported WCA-based ELISA protocols [12, 21]. Generally, the reported prevalence may be influenced by insensitive ELISA assays used in routine health monitoring, as shown here for one commercial assay.…”
Section: Discussionsupporting
confidence: 52%
“…Indirect R. pneumotropicus - or R. heylii -specific serological assays, such as enzyme-linked immunosorbent assay (ELISA), have not been described to the best of our knowledge. Currently, applied ELISA rely on inactivated whole cells detecting both P. pneumotropica biotypes Jawetz and Heyl [12, 13]. Manning et al reported a sensitive detection of P. pneumotropica antibodies based on a preparation of uncharacterized cell wall proteins, which were not examined for their specificity to Jawetz and Heyl isolates [14].…”
Section: Introductionmentioning
confidence: 99%
“…The Federation of Laboratory Animal Science Association (FELASA) lists P. pneumotropica as an important pathogen in mice, rats and hamsters and recommends the examination every 3 months [ 16 ]. Various monitoring methods are described including PCR [ 4 , 5 , 17 ] and indirect enzyme-linked immunosorbent assays (ELISAs) [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, serology has been employed, along with other diagnostic methodologies, to monitor laboratory animals for infections with fastidious bacteria such as Clostridium piliforme (Riley et al, 1994;Waggie et al, 1987), Helicobacter hepaticus , and CAR bacillus (Lukas et al, 1987b;Matsushita et aL, 1987). Serologic assays have also been developed for gram-negative bacteria such as Pasteurella pneumotropica (Boot et al, 1995), P. multocida (Lukas et al, 1987a), and Bordetella bronchiseptica from which specific lipopolysaccharide antigen can be purified (Manning et al, 1987).…”
Section: Serology For Detection Of Antibodies To Infectious Agentsmentioning
confidence: 99%